Analysis of Business Development Strategies in Increasing Customer Trust - Leonardo Sihombing; Herman Dinus (Journal on Economics, Management and Business Technology, 2024)
This research investigates the pivotal role of business development strategies in increasing customer trust within contemporary market environments. Through a comprehensive analysis of data collected using a mixed-methods approach, the study examines the efficacy of various strategies, including customer-centricity, transparency, and ethical conduct, in fostering trust-based relationships. Findings reveal that businesses that prioritize customer-centric practices, transparency in communication, and ethical conduct are more successful in cultivating trust among their customers. These insights are aligned with existing theoretical frameworks such as social exchange theory, the service quality model, and trust-commitment theory, contributing to theory development in the field of trust-based relationship management. Practical implications derived from the analysis offer actionable recommendations for businesses seeking to enhance customer trust through strategic initiatives, emphasizing the importance of aligning strategies with trust-building imperatives, integrating trust-building principles into organizational culture and operations, and continuously monitoring and adapting approaches. Overall, this research underscores the significance of trust as a fundamental driver of organizational success, highlighting its role as a catalyst for fostering enduring relationships with customers and driving long-term value creation.